The characteristics of the clinical method in Psychiatry - Ricardo Ángel González Menéndez (Medisur)
Some considerations about the clinical method in psychiatry are made. There are pointed out the present world context of medical care, the deterioration of the doctor patient relationship and also the clinical method, as sequeales of wrong use of technology, the privatization of medical care and the negative influence of yellow press and claims of lawyers. The author explains the specifities of the clinical method in a comprehensive medical care for psychiatric patients. It is emphasized the importance of developing adequate health team-patient-relative relationships, especially to fulfill the stages of the medical interview in these patients, who are needed of respect, understanding, help disposition and no judging.